Предмет: Математика,
автор: merekekaldygul
Sind cos3d+cos dsin3d
Ответы
Автор ответа:
1
2sin((3d-d)/2)cos((3d+d)/2)/(-2sin((3d-d)/2)sin((3d-d)/2))
в результате отнимания и деления получается:
2sind cos2d/(-2sind sin2d)= -cos2d/sin2d=-ctg2d
в результате отнимания и деления получается:
2sind cos2d/(-2sind sin2d)= -cos2d/sin2d=-ctg2d
nonik0123:
правильно?
Похожие вопросы
Предмет: Литература,
автор: rodionova1951001
Предмет: Обществознание,
автор: ASDADFADFA
Предмет: Музыка,
автор: daniilgorskij925
Предмет: Литература,
автор: ИванШвец